Teaching English Amidst Covid19 Pandemic: A Cross-level Educators’ Perception - Sonia Octavia; Agus Dwiyanto; Heni Noviarita (Jurnal Pendidikan dan Pengajaran, 2021)
The impact of the corona virus makes it difficult for teachers and students to adjust learning. The purpose of this study is to analyze as well to investigate the phenomenon of teaching English online amidst the re-emerging pandemic situation forcing the teaching learning process to be re-implemented online. The subjects were 10 cross-level English teachers situated in Java and Sumatra. Qualitative approach utilizing semi-structured interview method in obtaining the necessary data was chosen as the best method and approach in the study. The participants mainly agreed with the online learning system, though they faced challenges like limited subsidiary quotas, students' poor conditions, students' misbehavior and lack of better equipments. Besides various approaches and solutions in facing the challenges, it was also known that writing was considered the most challenging to teach among the four basic skills. The implication of this study endeavor the insights on tackling down the challenges of teaching amidst a pandemic. Synergy among so many elements like cross-level teachers, students, parents and policy makers was badly demanded to make the progress of online learning comes to betterment.